Pastoral Theology in an age of uncertainty - Graham, Elaine L. (HTS teologiese studies, 2006)
In this article the history of pastoral and practical theology is viewed through the lens of postmodern thought. The article argues that an “age of uncertainty” has been engendered by the dissolution of many of the scientific, political and philosophical nostrums of Western modernity. Such a characterization is, however, intended to present postmodernity more as a loss of innocence than the absolute annihilation of value. It is still possible to pursue the prospects for coherent theological reflection and faithful action amidst such a fracturing of certainties. That involves searching for ways of inhabiting consistently and authentically a tradition of binding values that recognize their own contingency but also seek to create some degree of coherence and transparency. The discipline of Practical Theology should be reconceived as the articulation and excavation of sources and norms of Christian practice, the discipline that enables the community of faith to practice what it preaches. This article is a reprinted version of chapter two of the author’s book Transforming practice: Pastoral Theology in an age of uncertainty, 1996, pp 38-55. Permission for republication is granted by Wipf and Stock Publishers, Eugene OR.What is